Inovasi Olahan Onde Wa’ai Varian Rasa Kekinian Dalam Meningkatkan Kreativitas Mahasiswa Dalam Berwirausaha - Bantas, Maria Goretty D; Dhiki, Yasinta Yenita; Aje, Ariswan Usman; Suryani, Lely; Se’a, Elisabeth Elviana; Malo, Benedikta; Yju, Quirinus; Sara, Albertus Novembriyano; Mandona, Kartika Chandra Kirana (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2023)
The entrepreneurial student creativity program (PKM-K) is a student creativity program for creating business activities; through the PKM-K program, students have a sample opportunity to realize creative ideas for products (goods and services), innovate to create new products and increase competence, insight, and experience in entrepreneurship. It is hoped that pk-k can be the forerunner to the emergence of business products in Indonesia as the nation’s independent work. It is hoped that creative product ideas from the nation’s young generation can be realized well so they can have a good influence on other young people. One student’s creative idea was OWADE (modern processed Onde Wa’ai), a contemporary snack based on local Pangan with chocolate, cheese, brown sugar, and fish floss flavors. To find out the effectiveness of innovation in current flavor variants in increasing students’ interest in onde snacks, a Wade product survey was conducted on students by taking a sample of 100 students and ten lecturers at the Flores University of Mathematics education study program. The result of this research was that 85% of students said they liked Owade products and would buy this product again. Looking at the survey results, the effectiveness of the current flavor variants in on-de snacks is quite large. In this way, the existence of Onde snacks will increase again and not be lost due to the flow of modernization.